Reporting Vaccine Complications: What Do Obstetricians and Gynecologists Know About the Vaccine Adverse Event Reporting System?. (8th September 2013) - Eckert, L. O.; Anderson, B. L.; Gonik, B.; Schulkin, J.
Abstract : Background . Obstetrician-gynecologists are increasingly called upon to be vaccinators as an essential part of a woman's primary and preventive health care. Despite the established safety of vaccines, vaccine adverse events may occur. A national Vaccine Adverse Event Reporting System (VAERS) is a well-established mechanism to track adverse events. However, we hypothesized that many obstetrician-gynecologists are naive to the role and use of VAERS. Methods . We devised a ten-question survey to a sample of ACOG fellows to assess their knowledge and understanding of VAERS. We performed descriptive and frequency analysis for each of the questions and used one-way analysis of variance for continuous and chi-squared for categorical variables. Results . Of the 1000 fellows who received the survey, 377 responded. Only one respondent answered all nine knowledge questions correctly, and 9.2% of physicians had used VAERS. Older physicians were less familiar with VAERS in general and with the specific objectives of VAERS in particular (χ 2 = 10.7, P = .005 ). Conclusions . Obstetrician-gynecologist familiarity with VAERS is lacking. Only when the obstetrician-gynecologist is completely knowledgeable regarding standard vaccine practices, including the availability and use of programs such as VAERS, will providers be functioning as competent and complete vaccinators.